Plant communities of travertine outcrops of the Saturnia area in southern Tuscany (central Italy) - Viciani, Daniele; Maffei, Barbara; Selvi, Federico (Hacquetia, 2015)
A phytosociological survey was carried out in a poorly known travertine area of southern Tuscany harbouring a rich vegetation mosaic with chamaephytic garrigues, species-rich xerophytic grasslands, chasmophytic coenoses, annual species-dominated communities, shrublands and thermophilous deciduous forests. Field sampling and data analysis allowed to identify and characterize several community types, some of which of significant interest due to their ecological specificity and rarity in peninsular Italy. In particular, our data confirm the associations Pistacio terebinthi-Paliuretum spinosae and Pistacio terebinthi-Quercetum pubescentis, respectively a shrub and forest community type previously unknown for Tuscany. In addition, a new therophytic association of travertine debris named Sedetum hispanico-caespitosi and placed in the Hypochoerion achyrophori alliance (Brachypodietalia distachyi order, Tuberarietea class) is also described. Finally, dynamic relationships between the vegetation types are highlighted and the presence of conservation priority habitats in the area are pointed out.